2014
DOI: 10.1017/s0033291714000683
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal maternal immune disruption and sex-dependent risk for psychoses

Abstract: Background Previous studies suggest that abnormalities in maternal immune activity during pregnancy alter the offspring’s brain development and are associated with increased risk for schizophrenia (SCZ) dependent on sex. Method Using a nested case–control design and prospectively collected prenatal maternal sera from which interleukin (IL)-1β, IL-8, IL-6, tumor necrosis factor (TNF)-α and IL-10 were assayed, we investigated sex-dependent associations between these cytokines and 88 psychotic cases [SCZ=44; af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 88 publications
(126 reference statements)
5
54
0
Order By: Relevance
“…Although some studies reported that high levels of proinflammatory cytokines during pregnancy were associated with worse outcomes in offspring [e.g., cerebral palsy (19), schizophrenia (21), and autism (22)], we recently reported that lower levels of maternal cytokines were associated with higher risk of depression and psychosis among female offspring (12,13). These studies are consistent with work by Kaukola and colleagues, who reported lower concentrations of IL-6 in cord blood associated with neurologic abnormalities at age 2 (47), and by Von Ehrenstein and colleagues, who reported that higher concentrations of IFN-γ and TNF-α in cord blood were protective against poor cognitive outcomes at age 7 y (18).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Although some studies reported that high levels of proinflammatory cytokines during pregnancy were associated with worse outcomes in offspring [e.g., cerebral palsy (19), schizophrenia (21), and autism (22)], we recently reported that lower levels of maternal cytokines were associated with higher risk of depression and psychosis among female offspring (12,13). These studies are consistent with work by Kaukola and colleagues, who reported lower concentrations of IL-6 in cord blood associated with neurologic abnormalities at age 2 (47), and by Von Ehrenstein and colleagues, who reported that higher concentrations of IFN-γ and TNF-α in cord blood were protective against poor cognitive outcomes at age 7 y (18).…”
Section: Discussionmentioning
confidence: 83%
“…Chan School of Public Health). We obtained prenatal serum samples acquired from mothers during early third trimester from the NIH repository (12,13). Concentrations of maternal cytokines were assessed by multiplexed immunoassays and analyzed in relation to the level of maternal socioeconomic disadvantage during pregnancy and clinical ratings of neurologic development of offspring during the first year of life.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…the association between prenatal rubella infection and cataract in 1941 (25). There is now a large body of work demonstrating that direct infection of the fetus with CMV, HSV-2, or rubella can cause major neurosensory deficits (26)(27)(28), learning disabilities, and psychiatric disorders (29)(30)(31). Microcephaly has also been associated with fetal CMV and ZIKV infection (ZIKV is further discussed below) (32,33).…”
Section: Viral Infection At the Maternal-fetal Interfacementioning
confidence: 99%